(untitled) (Research, Society and Development, 2021)
Objective: to evaluate the effectiveness of ear acupuncture in undergraduate students with varying levels of stress. Materials and methods: This is a quantitative study of an experimental, controlled nature, with two groups: intervention and control. To define the sample of the participants, the Lipp Stress Signs and Symptoms Inventory - ISSL was used, followed by those who obtained positive stress had a weekly session of 15 minutes at 1 hour for four weeks. For the intervention group, the points chosen were: Shen Men, Liver, Lung/Heart, Kidney and anxiety. The control group had its points chosen according to the complaints pointed out. After the last session the students responded to the ISSL. Results: Twenty-seven students participated in the study and a significant relationship was found between gender, age, time of travel to college, number of transportation and participation in extracurricular projects. These were divided into intervention group (13) and control group (14). After ear acupuncture, in the intervention group, an increase of 30.7% of students without stress was obtained and in the control group, this increase was 64.3%, approximately twice as high as in the first. Final considerations: It is possible to conclude that the stress rates of the participants are close to those found in other studies, and that ear acupuncture proved to be a technique that can help reduce the signs and symptoms of stress in this population.